Temperature-dependent dynamic fouling on superhydrophobic and slippery nonwetting copper surfaces - Mousavi, S.M.A.; Pitchumani, R. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Presents, for the first time, temperature-dependent dynamic fouling on nonwetting surfaces.•Elucidates, for the first time, effects of texturing method and surface type on fouling behavior.•Nonwetting surfaces show up to 75% less scaling compared to regular surfaces.•Electrodeposited surfaces offer better scaling resistance compared to etched surfaces.•Presents Hill-Langmuir model, for the first time, to describe the time evolution of scaling. Bioinspired, superhydrophobic and slippery liquid infused surfaces that offer nonwetting characteristics have been explored in recent years for fouling mitigation. However, most of the studies are in the context of biofouling or under static immersion at ambient temperature conditions that are not reflective of the dynamic flow environment in practice. This article presents, for the first time, a systematic study of dynamic fouling of superhydrophobic (SHS) and slippery lubricant-infused surfaces (LIS) over a range of flow and temperature conditions. Copper metallic surfaces were textured via electrodeposition or etching and further functionalized to achieve SHS and, additionally, infiltrated with a lubricant to fabricate LIS. The nonwetting surfaces were studied for their fouling behavior in a rotating Couette flow of a supersaturated calcium sulfate solution at different rotational speed and temperature. Fouling mineral mass accumulation on the different surfaces was measured as a function of time over a period of days using inductively coupled plasma mass spectroscopy and the fouled surfaces were investigated using scanning electron microscopy. Both SHS and LIS showed superior anti-scaling performance at all ranges of variables. An analytical Hill-Langmuir model is presented, for the first time, to describe the time evolution of scaling within 20% accuracy over the range of parameters studied. The study is the first to juxtapose two surface texturing methods, electrodeposition and etching, and two nonwetting surface types, SHS and LIS, subject to a common suite of experiments to elucidate fundamental understanding of mineral fouling on nonwetting surfaces.